The deer hunter [videorecording (DVD)] - Cimino, Michael; De Niro, Robert; Cazale, John, 1936-1978; Savage, John, 1949-; Walken, Christopher, 1943-; Streep, Meryl (Legacy series (Universal City, Calif.), 2005)
Tracks a group of steelworker pals from a Pennsylvania blast furnace to the cool hunting grounds of the Alleghenies to the lethal cauldron of Vietnam. Shows what happens to friendship and courage under stress.